Self-supported bacterial cellulose/boehmite organic-inorganic hybrid films - De Salvi, Denise T. B.; Barud, Hernane S.; Caiut, Jose Mauricio A.; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Springer, 2012)
Self-supported organic-inorganic hybrid transparent films have been prepared from bacterial cellulose and boehmite. SEM results indicate that the BC membranes are covered by Boehmite and XRD patterns suggest structural changes on cellulose due to Boehmite addition. Thermal stability is accessed through TG curves and is dependent on Boehmite content. Transparency, as evaluated by UV-Vis absorption, increases with increasing content of boehmite suggesting application of these materials as transparent substrates for opto-electronic devices.
Keywords: Bacterial cellulose; Boehmite; Organic-inorganic hybrids